CONTENT IN TEACHING FOREIGN LANGUAGES - Panjiyeva Ro’zixol, Panjiyeva Ro’zixol (Журнал иностранных языков и лингвистики, 2021)
Choosing a suitable content is imperative in teaching foreign language. Knowing what to teach and how to teach helps teachers to focus the themes correctly. Differentiating between “content” and “aim” is important while choosing contents.